The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1051/0004-6361:20030364
|View full text |Cite
|
Sign up to set email alerts
|

Abundant gas-phase H2O in absorption toward massive protostars

Abstract: Abstract. We present infrared spectra of gas-phase H 2 O around 6 µm toward 12 deeply embedded massive protostars obtained with the Short Wavelength Spectrometer on board the Infrared Space Observatory (ISO). The ν 2 ro-vibrational band has been detected toward 7 of the sources and the excitation temperatures indicate an origin in the warm gas at T ex > ∼ 250 K. Typical derived gas-phase H 2 O abundances are ∼5 × 10 −6 −6 × 10 −5 , with the abundances increasing with the temperature of the warm gas. The inferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 30 publications
6
42
1
Order By: Relevance
“…Hot cores have long been known to show a rich chemistry with complex organic molecules. The same molecules we observe in emission in the T Tauri stars have also been detected in absorption in mid-infrared bands towards several hot cores using ISO (Lahuis & van Dishoeck 2000;Boonman & van Dishoeck 2003). The derived gas temperatures for the absorbing gas are in the same range as we found for the T Tauri stars.…”
Section: Comparison To Envelopes Outer Disks Comets and Hot Coressupporting
confidence: 82%
“…Hot cores have long been known to show a rich chemistry with complex organic molecules. The same molecules we observe in emission in the T Tauri stars have also been detected in absorption in mid-infrared bands towards several hot cores using ISO (Lahuis & van Dishoeck 2000;Boonman & van Dishoeck 2003). The derived gas temperatures for the absorbing gas are in the same range as we found for the T Tauri stars.…”
Section: Comparison To Envelopes Outer Disks Comets and Hot Coressupporting
confidence: 82%
“…13) shows almost no lines of gas-phase molecules in contrast to the spectra toward the intermediate-mass protostar LkHα225 (van den Ancker 2000) and massive protostars Boonman et al 2000). For example, the ν 2 ro-vibrational band of gas-phase H 2 O at 6 µm, which is strong toward most of the massive protostars (Boonman et al 2000) has not been detected toward AFGL 490, placing an upper limit on the total amount of gas-phase H 2 O present (Table 8). Since gas-phase H 2 O abundances are predicted to be enhanced in warm regions and shocks, this indicates that AFGL 490 is not a "hot" source throughout the envelope.…”
Section: Results From Iso-swsmentioning
confidence: 99%
“…For a dark cloud with a mean life time of 1 Myr, the total photodesorbed water would be 3.8 × 10 14 molecules cm −2 ∼ 0.4 ML. This is a low number compared to gasphase water abundance toward massive protostars ∼ 10 18 molecules cm −2 (Boonman et al 2000 andvan Dishoeck 2003) but in cold clouds, Zmuidzinas et al (1995) and Tauber et al (1996) have found that the gas-phase H 2 O abundance is low, ∼ 10 −8 to 10 −7 related to H 2 . Yeghikyan (2017), using the Cloudy code (Ferland et al 2013), calculated the effect of the irradiation on the abun-dance of water (ice and gas) in planetary nebulae (PN) for 1000 yr.…”
Section: Discussionmentioning
confidence: 96%